2020
DOI: 10.1002/ieam.4327
|View full text |Cite
|
Sign up to set email alerts
|

Application of General Unified Threshold Models of Survival Models for Regulatory Aquatic Pesticide Risk Assessment Illustrated with an Example for the Insecticide Chlorpyrifos

Abstract: Mathematical models within the General Unified Threshold models of Survival (GUTS) framework translate time-variable chemical exposure information into expected survival of animals. The GUTS models are species and compound specific and explicitly describe the internal exposure dynamics in an organism (toxicokinetics) and the related damage and effect dynamics (toxicodynamics), thereby connecting the external exposure concentration dynamics with the simulated mortality or immobility over time. In a recent scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Both the present study and the study by Focks et al [9] stress the need to shed better light on the applicability of (eventually adapted) GUTS models for implementation in regulatory risk assessments of neonicotinoids. Such studies should also account for the various parameters that are known to influence the modeling results, such as differences in the test compounds, experimental durations, and test species, including their size/sensitive life stage and sex [13,17,40], as well as the influence of pesticide mixtures on the predicted toxicity [41]. Huang et al [40], for example, demonstrated that females of the aquatic sowbug Asellus aquaticus were less sensitive to imidacloprid than males.…”
Section: Concluding Remarks and Indications For Future Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Both the present study and the study by Focks et al [9] stress the need to shed better light on the applicability of (eventually adapted) GUTS models for implementation in regulatory risk assessments of neonicotinoids. Such studies should also account for the various parameters that are known to influence the modeling results, such as differences in the test compounds, experimental durations, and test species, including their size/sensitive life stage and sex [13,17,40], as well as the influence of pesticide mixtures on the predicted toxicity [41]. Huang et al [40], for example, demonstrated that females of the aquatic sowbug Asellus aquaticus were less sensitive to imidacloprid than males.…”
Section: Concluding Remarks and Indications For Future Researchmentioning
confidence: 99%
“…For example, TKTD models from the family of General Unified Threshold models of Survival (GUTS) enable estimating survival probabilities for any time-variable exposure profile [15,16]. GUTS modeling results are species-and compound-specific and explicitly describe the internal exposure dynamics in an organism (toxicokinetics) and the related damage and effect dynamics (toxicodynamics), thereby connecting the external exposure concentration dynamics with the simulated mortality or immobility over time [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our collection, issues regarding model reliability were pointed out for one case of population and community model. While being more recently developed (Jager et al, 2011;Kooijman, 2009), TKTD models such as GUTS and DEBtox models are of high interest for ERA (Brock et al, 2021;EFSA PPR Panel, 2018a). They are ready to use in practice in a regulatory context for few organisms like aquatic macroinvertebrates, fish and macrophytes, and their potential is mentioned for other organisms like non-target arthropods (EFSA PPR Panel, 2015a).…”
Section: Characterization Of the Models Used In Reportsmentioning
confidence: 99%
“…The TD part makes the link between damages suffered by organisms due to internal bioaccumulated concentrations with observable effects on life history traits such as an increased mortality or a reduced growth. Combined TKTD models are recommended by EFSA to refine Tier-2 risk assessment, especially for plant protection products acting on aquatic organisms when exposed to time-variable exposure profiles (European Commission, 2013;Ockleford et al, 2018;Brock et al, 2020). In particular, the EFSA already considers ready-to-use for ERA the TKTD models dedicated to the prediction of survival over time, and the EFSA encourages more research for the other types of TKTD models, namely those based on the Dynamic Energy Budget (DEB) theory for growth and reproduction of ec-totherm species and those for macrophytes.…”
Section: Introductionmentioning
confidence: 99%